Presunción de inocencia y privación de la libertad en el sentido del fallo (Tema Central) - Ruiz Cabrera, María Alexandra (2024)
It is essential to address procedural issues regarding deprivation of liberty, as there is currently a heated discussion in Colombia regarding whether this right should be restricted once a guilty verdict has been issued, particularly when prohibitions exist regarding punitive benefits. Two contrasting positions are being considered in jurisprudence. The objective is to resolve that, when faced with a similar legal issue, two different alternatives are being decided upon, both of which affect the right to liberty and consequently, the various consequences of incarceration. Thus, we will begin by emphasizing the importance of liberty as a fundamental prerequisite, followed by the identification of the two opposing positions regarding the same situation, and subsequently, the significance of the role of the argumentative judge will be addressed. Utilizing a qualitative methodology, which involves studying the topic through jurisprudence, doctrine, and literature, it will be inferred that limitations on the right to liberty within a contested procedural scenario may stem from various evaluative positions, and therefore, only a plausible result derived from the guarantee of motivation is foreseeable.